2020
DOI: 10.3390/ijms21186934
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Phosphodiesterase 3B (PDE 3B) by Anthocyanin-Rich Fruit Juice Extracts and Selected Anthocyanins

Abstract: Phosphodiesterases (PDEs) are essential enzymes for the regulation of pathways mediated by cyclic adenosine monophosphate (cAMP). Secondary plant compounds like anthocyanins (ACs) can inhibit PDE activity and, consequently, may be beneficial for lipid metabolism. This study investigated 18 AC-rich juice extracts and pure reference compounds from red fruits for potential inhibitory effects on PDE 3B activity. Extracts were obtained through adsorption on Amberlite® XAD 7 resin. Based on this screening, the choke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Within the last years, it has been reported that polyphenols can influence the lipid metabolism in vitro and in vivo [ 8 , 16 , 38 , 39 ]. In our previous work, extracts from red fruit juices or concentrates like cranberry, red grape, or blueberry have proven to be potent inhibitors of the enzyme PDE 3B [ 28 ]. To identify fruit juice constituents which influence lipid metabolism, a fractionation of the three most potent extracts from chokeberry, cranberry, and pomegranate was performed, and the effects of the anthocyanin, copigment, and polymer fractions in three different in vitro assays (lipid accumulation, lipolysis, and PDE 3B activity) were investigated.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Within the last years, it has been reported that polyphenols can influence the lipid metabolism in vitro and in vivo [ 8 , 16 , 38 , 39 ]. In our previous work, extracts from red fruit juices or concentrates like cranberry, red grape, or blueberry have proven to be potent inhibitors of the enzyme PDE 3B [ 28 ]. To identify fruit juice constituents which influence lipid metabolism, a fractionation of the three most potent extracts from chokeberry, cranberry, and pomegranate was performed, and the effects of the anthocyanin, copigment, and polymer fractions in three different in vitro assays (lipid accumulation, lipolysis, and PDE 3B activity) were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro studies have also examined the effects of polyphenol-rich extracts on lipid metabolism, as well as one of our previous studies [ 20 , 28 , 41 ]. Kowalska et al revealed that a berry fruit extract obtained from chokeberry, raspberry, bilberry, and cranberry fruits ( c = 25–100 µg/mL) significantly decreased lipid accumulation in 3T3-L1 cells without showing cytotoxicity [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations